Strategic Management of Islamic Education: Building Vision, Mission, and Synergy for Strategic Change - Ridwan, Mohammad; Indriana, Nina; Hisniati, Sally Badriya; Hidayat, Ara (CV. Tripe Konsultan, 2025)
Strategic management is an important element in ensuring the sustainability and relevance of Islamic education institutions amid the dynamics of global change. This article aimed to analyze the strategic management of Islamic education with a focus on the role of vision, mission and synergy as the foundation in creating strategic change. This research uses the literature study method to examine key concepts in Islamic education strategic management and their practical applications. The results show that vision provides an inspiring long-term direction, mission defines the main goals that distinguish the institution, while synergy enables effective coordination between organizational elements to achieve common goals. These three elements, when strategically designed and implemented, are capable of creating significant change that supports institutional transformation. The article also identifies key challenges that Islamic education institutions often face, including resistance to change, lack of coordination and limited resources, and offers strategic solutions to overcome them. By building synergy between vision, mission and implementation strategies, Islamic education institutions can optimize their role in responding to the needs of the times without abandoning their fundamental values. This study is expected to be a reference for Islamic education managers in developing innovative and sustainable strategies.